Grain-128a: a new version of Grain-128 with optional authentication. (12th December 2011) - ?gren, Martin; Hell, Martin; Johansson, Thomas; Meier, Willi
A new version of the stream cipher Grain-128 is proposed. The new version, Grain-128a, is strengthened against all known attacks and observations on the original Grain-128, and has built-in support for optional authentication. The changes are modest, keeping the basic structure of Grain-128. This gives a high confidence in Grain-128a and allows for easy updating of existing implementations.